Locality of building orientation in traditional Indonesian architecture: A systematic literature review - Hasan, Muhammad Ismail (Faculty of Built Environment, University of Malaya, 2022)
This study elucidates values that determine traditional Indonesian housing orientations. The diversity of cultures in Indonesia generates a firm rule in housing design and affects some elements, encompass housing orientation. Recent research on the orientation of locality-based buildings has not been much explained holistically, so this can be a potential for further discussion. In order to produce a synthesis of the orientation values, this research employs a systematic literature review from scientific papers on Scopus with certain screening processes. In brief, the results show nature, main access, and beliefs that determine the orientation of traditional Indonesian housings. Nature's role determines the orientation where dwellers respect nature, cultivate and prevent the wind. Main access also simply determines the housing orientation where transportation access is located. Furthermore, ancestors' beliefs, sacred space, and Qiblah also establish the housing orientation of traditional Indonesian housings. These results provide important insights into the development of traditional Indonesian housing knowledge that considers local culture, sustainable issues, and Islamic values. © 2022, University of Malaya. All rights reserved.